KEGEMUKAN, ANEMIA, DAN PRESTASI BELAJAR SISWA SEKOLAH DASAR DI KOTA BOGOR - Heryati, Lilis; Setiawan, Budi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The purpose of this study was to analyze the correlation between overweight, anemia, and academic achievement of elementary school students in Bogor District. The design of this study was a cross-sectional and it was conducted between March to July 2014, at Polisi 1 and At Taufiq elementary school. Total subjects were 100 students, consisting of 62 students (62%) with normal nutritional status and 38 students (38%) overnutrition (overweight and obese). Mann Whitney test, Independent sample t test, Spearman and Pearson correlation test were applied to analyze the variables tested. The results showed that there were a significantly different intake of energy, protein, and fat (p<0.05), but not for anemic status and academic achievement among normal nutritional status and overnutrition of the subjects. A significant correlation was found between energy intake and nutritional status (p<0.05), anemic status and the mean scores of science and Indonesian language subjects (p<0.05). However, there were no significant correlation among nutritional status with anemic status and academic achievement (p>0.05).